Radial distribution of wood extractives in European larch Larix decidua by TOF-SIMS imaging. (June 2018) - Fu, Tingting; Elie, Nicolas; Brunelle, Alain
Abstract: Wood extractives in the xylem of European larch Larix decidua were mapped by time-of-flight secondary ion mass spectrometry (TOF-SIMS) imaging, which allows the radial distribution of both mineral and lipophilic extractives in the xylem to be scrutinized with high spatial resolution for the first time. Results show that all the components are inhomogeneously distributed across the annual ring. Mineral nutrients including Na +, K +, Ca +, and Cl − ions exhibit no preferential localization between earlywood and latewood, whereas PO3 − ion is exclusively present in the ray cells, indicating it may be related to acid phosphatase. Lipophilic extractives were found to be more abundant in the inner secondary xylem. Ion images with 400 nm spatial resolution reveal that fatty acids, triglycerides and phytosterols are co-localized principally in the earlywood within the first annual ring. Resin acids prove to be the main components in the resin canal of the secondary xylem and are distributed in the outer of it. Graphical abstract: Highlights: Mass spectrometry imaging of wood extractives in European larch Larix decidua. Measurement of the radial distribution of mineral and organic compounds. Inhomogeneous distribution of the components across the annual ring.